Civil Legal Liability of Doctors in Malpractice Cases Due to Violations of Informed Consent - Aulia, Nabita; Silitonga, Vero Dumonda; Edwin, Edwin (Universitas Negeri Gorontalo, 2025)
Introduction: The purpose of this study is to examine the civil legal liability of doctors in malpractice cases resulting from violations of informed consent.Method: This study employs a normative legal research method, utilizing both statutory and conceptual approaches.Results: The results of the study indicate that informed consent must be given to patients before medical action is taken, and if there is medical negligence in providing medical services, then the doctor who commits the negligence can be held criminally responsible as stated in “Article 1365, 1234, 1320 of the Indonesian Civil Code.”Conclusion: Informed consent plays a crucial role for both patients and doctors, and failure to obtain it before a procedure can result in an unlawful act if negligence occurs, leading to harm to the patient. Keywords: Informed consent, malpractice cases, responsibility on civil legal liability